PKM USAHA PANGAN LOKAL PEMBUATAN OPAK UBI RASA MANIS - Zaldy Kurniawan Zaldy; Ilham Ary Wahyudie (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
In line with the increasing market demand, some cassava is cultivated in Indonesia. As a food ingredient, cassava has advantages compared to other food ingredients. One of the growing home industries that produces snacks in the form of cassava-based opaque. The survey was conducted at PKM for the manufacture of sweet potato opaque with cassava-based ingredients produced by the home industry